The post‐traumatic colour change of primary incisors: a colourimetric and longitudinal study. Issue 4 (15th September 2015) - Hyun, Hong‐Keun; Shin, Teo Jeon; Kim, Young‐Jae
Abstract : Background: Tooth colour change after trauma has been described subjectively as ranging from yellow/pink to grey/black. Aim: To investigate the longitudinal colourimetric change of post‐traumatic discoloured primary incisor using an intraoral colourimeter. Design: A total of 34 primary incisors from 15 boys and eight girls were studied. The mean post‐injury day during clinic visits (SD) and number of visit was 205.4 (194.8) and 3.9 (2.0). CIE L* (lightness), a* (green‐red) and b* (blue‐yellow) of the maxillary primary incisors were measured at every visit. The colour difference (Δ E* ab ) was calculated between the traumatized tooth and the control. Scatter graphs were made depicting the colour change of discoloured teeth and the Δ E* ab over time. Results: Mean CIE L *, a * and b * of the unaffected control were 80.8 (2.29), 0.9 (0.77) and 13.1 (2.67), respectively. L * gradually decreased to 70.7 (on day 71), then slowly recovered. a * increased to 3.7 (day 29) and decreased slowly. b * only demonstrated a small change that was within the control range during the follow‐up. Δ E* ab increased to 9.58 (day 56) and decreased slowly. Conclusion: The earlier recovery of a * was followed by the recovery of L *. During the post‐traumatic period, Δ E* ab failed to reach the clinically acceptable threshold.